(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article covers the theoretical foundations and practical aspects of the methodology for teaching the section "Food Preparation Technology" in technology lessons in secondary schools . The traditions of Uzbek national cuisine, effective methods of teaching modern culinary technologies to students, and pedagogical approaches used in the lessons are analyzed.